Volume 1: Symposia, Parts A, B and C 2009
DOI: 10.1115/fedsm2009-78150
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Particle Tracking Velocimetry in Fluidized Beds

Abstract: Fluidized beds are commonly found in the chemical and energy processing industries because of their low pressure drop, uniform temperature distribution, and high heat transfer rates. For example, in biomass gasification, biomass particles are injected into a heated bubbling bed of inert material (typically refractory sand) that volatilizes to form a flammable gas. However, the movement of the biomass particle through the bubbling bed is difficult to quantify because the systems are opaque. This paper describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…One type of fluidized bed operation involves the gasification of injected biomass particles. X-ray particle tracking is an excellent experimental technique to track the simulation of particle injection into a fluidized bed [12,24].…”
Section: Sample Particle Tracking In a Fluidized Bedmentioning
confidence: 99%
See 3 more Smart Citations
“…One type of fluidized bed operation involves the gasification of injected biomass particles. X-ray particle tracking is an excellent experimental technique to track the simulation of particle injection into a fluidized bed [12,24].…”
Section: Sample Particle Tracking In a Fluidized Bedmentioning
confidence: 99%
“…[12,24]. They showed that they can successfully track large intruder particles (~9 mm in diameter) in a fluidized bed composed of 500-600 f .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…al. [21]. However, the algorithm used was a native function in MatLab; for this study, the normalized cross-correlation is coded into the X-ray acqu isition and analysis software.…”
Section: Particle Tracking and Edge Detectionmentioning
confidence: 99%